Structural elements that regulate pp59c-fyn catalytic activity, transforming potential, and ability to associate with polyomavirus middle-T antigen. - Cheng, S H (1991)
Except for its unique amino-terminal region (residues 1 through 83), which possibly dictates substrate recognition, pp59c-fyn bears a high degree of homology with other members of the src family of tyrosine kinases. Here we show that the carboxy terminus of pp59c-fyn is necessary for stable middle-T-antigen association, that pp59c-fyn is normally phosphorylated on both serine and tyrosine residues, and that Tyr-531 and Tyr-420 are phosphorylation sites in vivo and in vitro, respectively. Analysis of a spontaneously generated mutant encoding a truncated form of pp59c-fyn and of variants specifically mutated at the Tyr-531 and Tyr-420 phosphorylation sites indicates that pp59c-fyn has regulatory elements analogous to those that have already been identified for other src-like tyrosine kinases. However, further examination of the pp59c-fyn variants suggests the likelihood of additional means by which its activities might be regulated. Although alteration of Tyr-531 to phenylalanine (531F) in pp59c-fyn results in a protein which is more active enzymatically that the wild type, the enhancement is much less than that for the analogous variant of pp60c-src. Furthermore, contrary to results of similar experiments on other src-like proto-oncogene products, 531F did not induce transformation of NIH 3T3 cells. Studies involving pp59c-fyn-pp60c-src chimeras in which the unique amino-terminal sequences (residues 1 through 83) of the two kinases were precisely interchanged implied that the inability of 531F to induce transformation is probably not caused by the absence of substrates for pp59c-fyn in NIH 3T3 cells but rather by the insufficient enhancement of pp59c-fyn kinase activity. It is therefore probable that the kinase and transforming activities of pp59c-fyn are repressed by additional regulatory elements possibly located in the amino-terminal half of the molecule.